Synthesis, characterization and irritant effects of nonivamide irritant riot control agent based on ionic liquids - Ma, Weiting; Wang, Hongying; Wang, Zhenxiong; Chen, Dong; Yuan, Ling; Qin, Liang; Mei, Zongshu (Frontiers in Chemistry, 2024)
Active Pharmaceutical Ingredients-Ionic liquids (API-ILs) can increase drug solubility and bioavailability of solid drugs without changing the structure of drug molecules. In the present work, nonivamide (pelargonic acid vanillylamide, PAVA) was used as the active drug and choline (Ch) and citric acid (CA) were selected as the ions to prepare PAVA–based ionic liquid ([Ch][PAVA] and [PAVA]3 [CA]), respectively. The characterization and physical properties of [Ch][PAVA] and [PAVA]3 [CA], such as FT–IR spectra, 1H NMR spectra, thermal stability and hydrophilicity, were investigated. And the irritant effects of the PAVA–based ionic liquids were measured by the animal irritation experiment. [Ch][PAVA] has higher decomposition temperatures, better hydrophilicity and comparable irritant effects. The results show that the PAVA–based ILs synthesized in this study may potentially serve as a promising novel riot control agent.